(untitled) (Research, Society and Development, 2021)
User absenteeism in the health system consists of not attending the scheduled appointments and scheduled procedures at SUS. The objective of this project was to identify the factors that influence the absenteeism of UBS patients in scheduled appointments. This is an exploratory, descriptive study with a qualitative approach. The collection instrument was telephone interview, which one was taken from the consultation books of UBS Laranjeiras - Marabá / PA. Descriptive statistical analysis of the participants’ profile and content analysis were used to research the reasons for absences and the patient’s understanding of this act consequences. The profile of the participants was mainly female (75%), non-white (96.8%), with a mean age of 33.9 years and 66.7% were unemployed at the time of the interview. The management of the unit, the inadequacy of the scheduled appointments dates, the difficulty with the users’ displacement to the UBS, environmental factors, the doctor-patient relationship and the patient’s lack of knowledge about the procedures were found as motivators of absenteeism. Patients’ perception of absenteeism consequences showed users who recognized the damage that could be caused to other users or themselves and patients who were unaware of or neglected this damage. Finally, it must be recognized that there are difficulties in relation to the communication between the user and the UBS and, thus, look for alternatives that reduce existing noise and that allow a better contact between the subjects.